IMPROVING THE SOCIO-POLITICAL FOUNDATIONS OF CIVIL SOCIETY INSTITUTIONS IN NEW UZBEKISTAN - Ikramjon Batirovich Masharipov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the measures aimed at the formation of civil society and the improvement of its institutions in New Uzbekistan. It also examines the mechanisms of democratization, the cooperation between the state and civil society, the achievements gained in this direction, and the existing challenges. Within the framework of the study, new mechanisms and models emerging in the process of developing civil society are analyzed, with a focus on elaborating scientific-theoretical and practical recommendations.